Food insecurity, social networks and symptoms of depression among men and women in rural Uganda: a cross-sectional, population-based study. Issue 5 (9th October 2017) - Perkins, Jessica M; Nyakato, Viola N; Kakuhikire, Bernard; Tsai, Alexander C; Subramanian, SV; Bangsberg, David R; Christakis, Nicholas A
Abstract: Objective: To assess the association between food insecurity and depression symptom severity stratified by sex, and test for evidence of effect modification by social network characteristics. Design: A population-based cross-sectional study. The nine-item Household Food Insecurity Access Scale captured food insecurity. Five name generator questions elicited network ties. A sixteen-item version of the Hopkins Symptom Checklist for Depression captured depression symptom severity. Linear regression was used to estimate the association between food insecurity and depression symptom severity while adjusting for potential confounders and to test for potential network moderators. Setting: In-home survey interviews in south-western Uganda. Subjects: All adult residents across eight rural villages; 96 % response rate ( n 1669). Results: Severe food insecurity was associated with greater depression symptom severity ( b =0·4, 95 % CI 0·3, 0·5, P <0·001 for women; b =0·3, 95 % CI 0·2, 0·4, P <0·001 for men). There was no evidence of effect modification by social network factors for women. However, for men who are highly embedded within in their village social network, and (separately) for men who have few poor contacts in their personal network, the relationship between severe food insecurity and depression symptoms was stronger than for men on the periphery of their village social network, and for men with many poor personal network contacts, respectively. Conclusions: In this population-based study from rural Uganda, food insecurity was associated with mental health for both men and women. Future research is needed on networks and food insecurity-related shame in relation to depression symptoms among food-insecure men.